Hermeneutika sebagai Metode Ilmu Kemanusiaan (Perspektif Hermeneutika Wihelm Dilthey) - I Ketut Wisarja (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Since Auguste Comte period, natural science dominated the development of scientific methodes and even used in social, humanities, and cultural sciences. In the end of 19th century, any consciousness of unsuffcient method of natural science was begun. Wihelm Dilthey (1833-1911) started using new way. He was a person who attempted to differ geisteswissenschaft and naturalwissenschaft to make different method. He introduced hermeneutics as an alternative method for humanities.